The preparation of social studies teachers in the University of the Philippine and its implications for the preparation of social studies teachers in Malaysia - Kamal, Hanafi Bin Mohamed 1943- ([Quezon City s.n.], 1971)
The programme for the preparation of social studies teachers in the College of Education, University of the Philippines was examined. This includes the structure of and admission procedures into the programme, curriculum-general education, professional education, subject specialization and co-curricula activities, student teaching, teacher educators and social studies educators, and views of prospective social studies teachers and some selected graduate social studies teachers regarding the programme. It sought to draw some implications derived there from for the preparation of social studies teachers in Malaysia. Content analysis and the normative study method were utilized.
Thesis (M. Ed.)--University of the Philippines.
Keywords: University of the Philippines (Diliman) -- College of Education; Social science teachers -- Philippines; Social science teachers -- Malaysia